The second international symposium on tilapia in aquaculture. - Pullin, RSV; Bhukaswan, T.; Tonguthal, K; and Maclean, JI. (Manila, Philippines ICLARM, 1988)
ICLARM Contribution No.530
Keywords: Aquaculture; Tilapia culture